2013
DOI: 10.1371/journal.pone.0059634
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Calcineurin Activity after Lung Transplantation: A 2-Year Follow-Up

Abstract: The objective of this pharmacodynamic study was to longitudinally assess the activity of calcineurin during the first 2 years after lung transplantation. From March 2004 to October 2008, 107 patients were prospectively enrolled and their follow-up was performed until 2009. Calcineurin activity was measured in peripheral blood mononuclear cells. We report that calcineurin activity was linked to both acute and chronic rejection. An optimal activity for calcineurin with two thresholds was defined, and we found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Therefore, using TAC intra-PBMC concentration would be a surrogate marker easier to implement in clinical practice. Among pharmacodynamic parameters reflecting TAC effect, the clinical utility of CaN activity measurement was reported by several authors [8,36,37] and an important interpatient variability was described in their works as in our study. Such a variability as well as the imperfect correlation observed with the intracellular concentration (r = À0.5) could be explained by wild differences in the relative level of FK binding protein (FKBP) isoforms in PBMC from different patients [38].…”
Section: Discussionsupporting
confidence: 63%
“…Therefore, using TAC intra-PBMC concentration would be a surrogate marker easier to implement in clinical practice. Among pharmacodynamic parameters reflecting TAC effect, the clinical utility of CaN activity measurement was reported by several authors [8,36,37] and an important interpatient variability was described in their works as in our study. Such a variability as well as the imperfect correlation observed with the intracellular concentration (r = À0.5) could be explained by wild differences in the relative level of FK binding protein (FKBP) isoforms in PBMC from different patients [38].…”
Section: Discussionsupporting
confidence: 63%
“…Different investigations have reported that liver transplant recipients experiencing ACR exhibit higher calcineurin activity than those without a rejection episode, suggesting a lower pharmacological impact of TAC [16][17][18]. This increased calcineurin activity within a graft rejection episode has also been confirmed in patients after lung [35], renal [36] or liver transplantation [18]. The question raised…”
Section: Capron Et Al Have Recently Documented That Low Tac Concentrmentioning
confidence: 92%
“…acute cellular rejection [24][25][26]. A few studies, conducted in liver transplantation, described the pharmacokinetic-pharmacodynamic relationship of TAC by studying the link between whole blood concentrations and CaN activity in PBMC [27][28][29].…”
Section: Plos Onementioning
confidence: 99%